AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DALAM PERSPEKTIF BUDAYA TRI HITA KARANA - Komang Adi Kurniawan Saputra; Putu Budi Anggiriawan; I Nyoman Sutapa (Universitas Airlangga, 2018)
The purpose of this study is to gain an understanding of accountability practices in village financial management in Desa Pakraman Kerobokan, Sawan District, Buleleng Regency. This research with qualitative method through etnometodology approach to approach setting in everyday life. Tri hita karana's data and philosophy as a framework for analyzingthe data obtained from those settings on the research site. The results of this study indicate that in the perspective prahyangan spiritual accountability reflected in the reflection of devotion and faith of village finance managers or village apparatus with activities based on the values and norms contained in religious teachings, and the spirit of work that is seen as a sacrifice and devotion. The practice of accountability of village financial management in the dimensions of human relationships with the natural environment (ecological accountability) can be seen from the activities and involvement of the village apparatus in efforts to preserve the natural environment. And the accountability practices of human relations dimensions with others (economicand social accountability) can be seen from social concerns and various community empowerment programs. The contribution of this theoretical research is to contribute theoretical enrichment that underlies accountability practices in village administrationand its practical contribution, this research can be one of reference for rural apparatus, village companion in its advisory method.